Illumination of deformation by bending stresses and slab pull within the Southern Hikurangi Double Benioff Zone. Issue 1 (2nd January 2019) - Evanzia, Dominic; Lamb, Simon; Savage, Martha K.; Stern, Tim
ABSTRACT: Double Benioff Zones (DBZ) are ubiquitous in subduction systems worldwide, but the stress systems that give rise to them are not well known. We characterise stress orientations in the upper and lower bands of a DBZ in the dipping subducted Pacific plate beneath the southern Hikurangi margin, New Zealand. Stress orientations were calculated from focal mechanisms with 10 or more polarity picks, using a Bayesian stress inversion technique. The stress orientations in the upper band of seismicity are consistent with a down-dip extensional stress regime, whereas stress orientations within the lower band of seismicity are consistent with a down-dip compressional stress regime. This demonstrates that bending stresses are dominant within the Pacific plate beneath the southern North Island, possibly due to subduction beneath thickened mantle lithosphere of the Australian plate.